Teacher leadership in developing religious character in Muhammadiyah elementary school - Arum Titi Nurani; Suyatno Suyatno; Lilis Patimah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
The religious character dimension plays an important role in developing the character of elementary school age children as a whole. Teacher leadership is one variable that can be used to develop the religious character of elementary school age children. This research aims to explore teacher leadership in Muhammadiyah elementary schools in developing students' religious character. Researchers use qualitative research with a case study approach with observation, interviews and documentation as data collection techniques. The research subjects consisted of school principals, teachers and students at SD Muhammadiyah Macanan Sleman. The collected data was analyzed using the Miles & Huberman model of interactive inductive data analysis techniques which includes data collection, data reduction, data presentation and conclusions. To ensure the validity of the data, researchers used triangulation of sources and techniques. The research results show that teacher leadership in developing religious character at SD Muhammadiyah Macanan consists of three aspects, namely personal, team and organizational aspects. The personal aspect of teacher leadership is demonstrated by the ability to guide, mobilize, influence and communicate. The team aspect of teacher leadership is carried out by discussing and providing feedback, improving the quality of learning, training religious character, mentoring activities, and observing students' religious character. The organizational aspect of teacher leadership consists of the role of teachers in supporting school policies and programs, supporting the administrative leadership of the school principal, and efforts to maintain school sustainability. The findings of this research highlight the importance of the role of teacher leadership in developing students' religious character in Muhammadiyah elementary schools.